Effect of Merger and Acquisition Practice in Financial Institutions of Nepal - Shrestha, Prakash (Journal of Balkumari College, 2019)
The merger and acquisition serve as a disciplinary device for the bank management to improve the performance of the bank or as a means of implementing unpleasant business measure. This study aims to study the effect of merger and acquisition practice based on perceptions of personnel of financial institutions of Nepal. For the study, a closed-end questionnaire has been prepared and distributed among 180 banking personnel of three merged commercial banks (i.e. NIC Bank Ltd. and Bank of Asia Ltd., Global IME Bank Ltd. and Commerce & Trust Bank Ltd., and Prabhu Bank Ltd. and Grand Bank Nepal Ltd.) to analyze their views towards banking merger process. Out of them 80 (53.33%) questionnaires have been returned and used in this study. The results of this study indicate that merger and acquisition affect the liquidity position of the bank. The results also show that M&A practices increase the capital base of BFIs & thus develop the competent capabilities.